Impact of overlapping on 1‐year clinical outcomes in patients undergoing everolimus‐eluting bioresorbable scaffolds implantation in routine clinical practice: Insights from the European multicenter GHOST‐EU registry. Issue 5 (12th August 2016) - Ortega‐Paz, Luis; Capodanno, Davide; Giacchi, Giuseppe; Gori, Tommaso; Nef, Holger; Latib, Azeem; Caramanno, Giuseppe; Di Mario, Carlo; Naber, Christoph; Lesiak, Maciej; Capranzano, Piera; Wiebe, Jens; et al.
Abstract : Background: Overlapping implantation of bioresorbable scaffolds (BRSs) are frequent in long coronary lesions. Its impact on clinical outcomes is unknown. Objective: To compare the clinical outcomes of patients treated with overlapping BRS with those patients treated with no‐overlap BRS. Methods: We analyzed the 1‐year clinical outcomes of 1, 477 patients treated with BRS in the GHOST‐EU registry, according to the implantation of overlapping BRS. Primary endpoint was patient oriented composite endpoint (PoCE) of: all‐cause death, any myocardial infarction (MI) and any repeated revascularization. Scaffold thrombosis, according to Academic Research Consortium definition, was also analyzed. Results: A total of 320 (21.7%) patients were treated with overlapping BRS (overlap group), whereas the remaining 1, 157 (78.3%) received no‐overlap BRS (no‐overlap group). The overlap group had significantly higher frequency of male sex, diabetes mellitus, stable angina, B2/C lesion type, SYNTAX score ≥22, lesion length >34 mm, use of intracoronary imaging guidance, pre‐ and postdilatation. At 1‐year, there were no differences in PoCE between the overlap versus no‐overlap group (18.4% vs. 18.2%; HR 1.07, [0.80–1.44]; P  = 0.636), even after adjustment (HR 1.05, [0.48–2.20]; P  = 0.904). Scaffold thrombosis rate did not differ either at one‐month (1.3% vs. 1.5%, P  = 0.769) or at 1‐year (1.9% vs. 2.1%, P  = 0.823). Conclusions: In "Real‐world" clinical practice, overlapping BRS does not appear to have an impact on clinical outcomes as compared to no‐overlapping BRS. These preliminary data should be confirmed. © 2016 Wiley Periodicals, Inc.